Preparation of molecularly imprinted polymer for selective solid-phase extraction and simultaneous determination of five sulfonylurea herbicides in cereals - Liu, Yuan; Wang, Jian; Wang, Fengli; Han, Zhengzheng; Zhu, Xuran; Liu, Yang; Cheng, Ming; Song, Mengmeng; Wang, Rui; Wang, Tianrui; Miao, Yutian; Liu, Jia; et al. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Molecular imprinting polymer (MIP) has been increasingly employed for sulfonylurea herbicides (SUHs) detection in different matrices. A novel MIP that was effective as a highly class-selective sorbent in molecularly imprinted solid-phase extraction (MISPE) was successfully prepared for isolation and purification of SUHs, namely, metsulfuron-methyl, chlorsulfuron, chlorimuron-ethyl, prosulfuron, and pyrazosulfuron-ethyl, in rice, corn and soybean samples. The MIP was synthesized by precipitation polymerization using metsulfuron-methyl as the template, 4-vinylpyridine as the functional monomer, ethylene glycol dimethacrylate as the crosslinker, and MeCN as the porogen. The polymerization system of the MIP was optimized, and its adsorption performances were evaluated by comparing its adsorption isotherms and adsorption kinetics with those of a non-imprinted polymer (NIP). Following MISPE for extracting and enriching SUHs from rice, corn and soybean samples, high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) was performed. Acceptable recoveries were observed at SUHs contaminant concentrations of 10, 20 and 40 μg/L: from 77.56 to 99.81%, with relative standard deviations of <13.8% (n = 5) for all samples. The limits of detection for the five SUHs were 0.21-0.26 μg/L. The results demonstrated that the proposed MISPE-HPLC-MS/MS method is an effective approach for the simultaneous and sensitive determination of the five SUHs in rice, corn and soybean samples.